No evidence that visual exploratory activity distinguishes the super elite from elite football players - Caso, S.; McGuckian, T. B.; van der Kamp, J. (Science and Medicine in Football, 2025)
Visual exploratory activities (VEA) refer to head and body movements that football players make prior to receiving the ball to search possibilities for action. VEA is considered a key performance indicator that differentiates the skill level of players. This study revisited whether VEA also distinguishes super elite, award winning players from their elite teammates without awards. To this end, video footage from the men`s UEFA Champions League season 2018-2019 featuring the super elite players (n = 18) and the elite players (n = 18) was analyzed. To reduce the potential differences in match dynamics as much as possible, the selected players in the two groups were of the same team, playing the same match, in the same positioning line. VEA (i.e. frequency per unit time) during the penultimate and final pass prior to ball reception and performance (i.e. percentages of adequate ball contacts and subsequent actions) were compared between the two groups of players using ANOVA and Mann-Whitney tests, respectively. In addition, hierarchical stepwise regression analyses were conducted to explore the degree to which VEA was predicted by group and subsequent performance. The results showed that the players had higher VEA during the final pass (M = 0.45) than the penultimate pass (M = 0.41). There were no significant differences in VEA or performance between the two groups. Also, the regression analyses did not deliver significant models. We conclude that with partial control for match dynamics, no evidence emerged to support that VEA distinguishes super elite players from elite football players.